DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON CONTEXTUAL LEARNING CURRENT PKN STUDENTS OF CLASS V SDN 250/VI SINAR GADING II - Agung Wibowo; Deny Setiawan; Tappil Rambe (Sensei International Journal of Education and Linguistic, 2022)
This study aims to develop interactive learning media based on contextual learning in Civics subjects at SD Negeri 250/VI Sinar Gading II, the material of rights and obligations is used as a tool to support learning to be more effective and efficient. This interactive learning media is made with the help of articulate storylines by combining various kinds of objects, namely text, images, animation, audio, video, and interactive buttons. The media will be tested to determine the feasibility and practicality of the media. This research is a research and development. The development model used is the Akker model. The research development stage includes (1) problems with problems, (2) analysis, (3) media design and development, and (4) design evaluation or validation. The data collection technique used was using a questionnaire which was analyzed descriptively to determine the validity and practicality. The results of this study are interactive learning media based on contextual learning, with an average assessment of (1) the results of the validation assessment of two material experts on the aspects of the feasibility of content and presentation obtained an average value of 3.65 with a valid category, (2) the results of the validation assessment from two media experts on the media feasibility aspect and the graphic feasibility aspect obtained an average value of 3.80 with a valid or feasible category, (3) the results of the validation assessment of the instructional design expert by two experts with an average value of 3.86 in a good category, and (3 ) practical test of teacher users at SD Negeri 250/VI Sinar Gading II from three practitioners obtained an average score of 3.40 in the good or practical category. Conclusion Interactive learning media based on contextual learning is appropriate for use in the learning process on Civics subjects for fifth grade students at SD Negeri 250/VI Sinar Gading II